2001
DOI: 10.2113/gscanmin.39.4.937
|View full text |Cite
|
Sign up to set email alerts
|

Ore-Mineral Textures and the Tales They Tell

Abstract: Ore minerals have been the resource base for all metal used by humankind since the dawn of history. Total world production of refined metals has been approximately 62 billion tonnes, and today, annual production exceeds 1.3 billion tonnes. Ore minerals, whether concentrated in ore deposits or dispersed as accessory minerals, can provide valuable information on the origins, histories and, in some case, futures of the metals. The same metals that serve society in myriad uses also have the potential to become maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Most of the titanomagnetite grains show solid‐state oxidation‐exsolution features with a lamellae of ilmenite distributed in the Ti‐poor magnetite. These textures indicate a magmatic origin [ Craig , ; Turner et al ., ] (Figures a–c). We also observe titanomagnetite with oxidation‐exsolution features in samples SH13.3, SH18.4, and SH24.8, but note that the abundance is remarkably low (Figures d–l).…”
Section: Petrographymentioning
confidence: 99%
“…Most of the titanomagnetite grains show solid‐state oxidation‐exsolution features with a lamellae of ilmenite distributed in the Ti‐poor magnetite. These textures indicate a magmatic origin [ Craig , ; Turner et al ., ] (Figures a–c). We also observe titanomagnetite with oxidation‐exsolution features in samples SH13.3, SH18.4, and SH24.8, but note that the abundance is remarkably low (Figures d–l).…”
Section: Petrographymentioning
confidence: 99%
“…By means of orientation contrast (OC) imaging and electron backscatter diffraction (EBSD), Barrie et al (2010) concluded that the preservation of annealing textures in greenschist-facies metamorphosed massive sulfides of the Norwegian Caledonides potentially represented surface-driven processes (re-arrangement by a dissolution/syntaxial overgrowth) during metamorphism This conclusion contrasts with the classical assumption that foam textures result from recrystallization (e.g. Vokes, 1969;Cook et al, 1993;Velasco et al, 1998;Craig, 2001), which certainly occurs at higher than greenschist facies metamorphic grade (McClay and Ellis, 1983). This conclusion is in good agreement with the limited mobilization of gold during metamorphic upgrading observed in Cerro de Maimón ores (discussed in section 9.4).…”
Section: Accepted M Manuscriptmentioning
confidence: 95%
“…Wyborn et al, 1994;Holliday and Cook, 2007;Hagemann et al, 2007;Benavides et al, 2008;Tassinari et al, 2008;2015;Piercey, 2010;McCuaig et al, 2010;McCuaig and Hronsky, 2014;Huston et al, 2016;Smith et al, 2016;Groves et al, 2016;Codeço et al, 2018); (ii) distal manifestations of concealed ore systems by means of mineralogical and geochemical/isotopic criteria, which can also be used to discriminate targets with high metal contents and/or larger tonnage (e.g. Craig, 2001;Holk et al, 2003;Piché and Jébrak, 2004;Kelly et al, 2006;Kerrich and Wyman, 2007;Jackson, 2010;Cheng and Zhao, 2011;Dupuis and Beaudoin, 2011;Wang et al, 2012;Wilkinson et al, 2015;Zao et al, 2016;Champion and Huston, 2016;Dill, 2018;Gonçalves et al, 2018); (iii) combined data processing resulting from various geophysical methods and using inversion model techniques (e.g. Oldenburg et al, 2007;Laznicka, 2014;Inverno et al, 2015;Revuelta, 2018); and (v) joint analysis of physical properties and mineralogical/ geochemical data to better resolve potential targets (e.g.…”
Section: Figura 1 (A) La Masa Total Elemental Estima (Mi) Como Una Fmentioning
confidence: 99%